Hydrogeochemical Appraisal of Groundwater Quality and Suitability for Irrigation in Samoda Nala Watershed, Chhattisgarh, India, using Statistical and Geographic Information Systems - Kannukettymukalel I.; Dewangan R.; Jhariya D.; Kishore N. (My University, 2025)
The current study was carried out in the Samoda Nala watershed, Chattisgarh, India, to determine the spatial variation of groundwater chemistry, its relationship with hydrogeochemistry and other activities. A total of 45 groundwater samples and 13 surface water samples were obtained from the research region and submitted to various geochemical and geographic information system (GIS) studies in order to characterise the general state of the groundwater and surface water in the area. For the analysis of cations and anions, standard analytical techniques were used. Cations, such as Ca2+, Mg2+, Na+, K+ alongwith anion, like HCO3-, Cl-, F-, NO3-, SO42- were analyzed and compared with the BIS standard to find out the quality of water for drinking purposes. Among the anion and cation ions, the NO3- ion had a higher concentration in several samples (>38%) than the BIS permissible limit. Furthermore, the correlation analysis of the ions reveals that Cl-TDS, SO42-TDS, Mg2+-HCO3- and Na+-Cl- have strong positive correlation (>0.7) with each other. The findings, which were then plotted on various bivariate diagrams and the gibbs diagram, to determine the primary mechanism controlling the area's water quality, revealed that rock-water interaction is the most important factor. Furthermore, the GIS-based prediction of the water quality index in light of all of these key ions assisted in identifying locations with good, moderate and poor water quality. The quality of irrigation water demonstrates that SAR, RSC, USSL and Wilcox diagram projected samples in the safe zone, however, the samples calculated for the magnesium hazard reveal that approximately 31% of samples are unsuitable. Validation of the generated water quality index of the study area with reference to the NO3- concentration has given 91% accuracy of the obtained result. © 2023- Kalpana Corporation.